Oestrogen inhibits salt-dependent hypertension by suppressing GABAergic excitation in magnocellular AVP neurons. Issue 10 (22nd September 2020) - Jin, Xiangyan; Kim, Woong Bin; Kim, Mi-Na; Jung, Won Woo; Kang, Hyung Kyung; Hong, Eun-Hwa; Kim, Yoon Sik; Shim, Wan Joo; Han, Hee Chul; Colwell, Christopher S; Kim, Young-Beom; Kim, Yang In
Abstract: Aims: Abundant evidence indicates that oestrogen (E2 ) plays a protective role against hypertension. Yet, the mechanism underlying the antihypertensive effect of E2 is poorly understood. In this study, we sought to determine the mechanism through which E2 inhibits salt-dependent hypertension. Methods and results: To this end, we performed a series of in vivo and in vitro experiments employing a rat model of hypertension that is produced by deoxycorticosterone acetate (DOCA)-salt treatment after uninephrectomy. We found that E2 prevented DOCA-salt treatment from inducing hypertension, raising plasma arginine-vasopressin (AVP) level, enhancing the depressor effect of the V1a receptor antagonist (Phenylac 1, D-Tyr(Et) 2, Lys 6, Arg 8, des-Gly 9 )-vasopressin, and converting GABAergic inhibition to excitation in hypothalamic magnocellular AVP neurons. Moreover, we obtained results indicating that the E2 modulation of the activity and/or expression of NKCC1 (Cl − importer) and KCC2 (Cl − extruder) underpins the effect of E2 on the transition of GABAergic transmission in AVP neurons. Lastly, we discovered that, in DOCA-salt-treated hypertensive ovariectomized rats, CLP290 (prodrug of the KCC2 activator CLP257, intraperitoneal injections) lowered blood pressure, and plasma AVP level and hyperpolarized GABA equilibrium potential to prevent GABAergic excitation from emerging in the AVP neurons of these animals. Conclusion: Based on these results, we conclude that E2 inhibits salt-dependent hypertension by suppressing GABAergic excitation to decrease the hormonal output of AVP neurons. Graphical Abstract: